1977
DOI: 10.3109/00365517709101837
|View full text |Cite
|
Sign up to set email alerts
|

Carotid baroreceptor function in hypertensive patients

Abstract: Carotid baroreceptor function has been studied in twenty-five patients with essential hypertension and in ten normotensive control subjects of corresponding age. The carotid baroreceptors were stimulated by increasing the transmural pressure over the carotid arteries by the application of negative pressure in a box enclosing the neck. Stimulation elicited significant decreases in intra-arterial blood pressure, heart rate and cardiac index in both hypertensive and normotensive subjects. Both groups also showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…Both blood pressure and heart rate responses to sinusoidal neck suction decreased with increasing mean arterial blood pressure. With regard to the blood pressure response the results differ from previous studies in which (static) neck suction led to unchanged (Wagner, Wacherbauer & Hilger 1968, BevegArd, Castenfors & Danielsson 1977 or even enhanced responses (Mancia et al 1978) in hypertensive compared to normotensive subjects. With regard to the heart rate response the results correspond to those studies in which the arterial baroreceptors were stimulated either by brief (seconds) periods of neck suction (Eckberg 1979), or by transient drug induced blood pressure increases (Gribbin et al 1971, Korner et al 1974, Takeshita et al 1975, Randall et al 1976, Simon et al 1977, Mancia et al 1978.…”
Section: Discussioncontrasting
confidence: 97%
“…Both blood pressure and heart rate responses to sinusoidal neck suction decreased with increasing mean arterial blood pressure. With regard to the blood pressure response the results differ from previous studies in which (static) neck suction led to unchanged (Wagner, Wacherbauer & Hilger 1968, BevegArd, Castenfors & Danielsson 1977 or even enhanced responses (Mancia et al 1978) in hypertensive compared to normotensive subjects. With regard to the heart rate response the results correspond to those studies in which the arterial baroreceptors were stimulated either by brief (seconds) periods of neck suction (Eckberg 1979), or by transient drug induced blood pressure increases (Gribbin et al 1971, Korner et al 1974, Takeshita et al 1975, Randall et al 1976, Simon et al 1977, Mancia et al 1978.…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast, studies using sustained neck suction to change afferent baroreceptor activity have detected no indication of reduced baroreceptor responses (28)(29)(30). Thus, regarding both hypertension and mental stress, analogous discrepancies between results are obtained in studies analyzing baroreceptor responses to transient as opposed to sustained changes in blood pressure.…”
Section: Baroreceptor Reflexes During Mental Stressmentioning
confidence: 87%
“…Babaev et al [2] found that there was a negative correlation between the vasodepressor response to neck suction and the incidence of hypertensive crises. The effects of hypertension on the cardiac responses to neck suction seem less consistent with reports of augmented [55], blunted [79,80] and no differences in the responses [6]. To investigate further the involvement of the baroreflex in hypertension a number of studies have examined the effects of anti-hypertensive drugs.…”
Section: Hypertensionmentioning
confidence: 93%
“…Mancia et al [56], however, found no change in response to baroreceptor stimulation (although cardiac responses were measured using the phenylephrine method) but augmented responses to baroreceptor deactivation. Mefruside, alprenolol and clonidine have all been shown to have no effect on the responses to baroreceptor stimulation [6,53].…”
Section: Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation